(untitled) (COLOMBIAN JOURNAL OF ADVANCED TECHNOLOGIES, 2023)
Contributing to sustainability is a strategy that has allowed organizations to develop new trends in production activities and technological innovation, helping to mitigate the impact on the environment that the industry makes in the daily life of its processes and procedures, ranging from the reduction of industrial emissions to energy renewal. That is why, through this research, we want to present an alternative design for an industrial solution, revealing the technical aspects that lead to the development of an eco-sustainable thermoformer, that is, one that works through alternative energies, specifically solar energy, with a view to using cassava starch to assemble biodegradable dishes.